Simplified Target Strength Analysis Procedure of an Underwater Vehicle Considering Target Strength Absorbing Materials - Jangwoo Kim; Jaeman Kim; Joo-Yeob Lee; Dae-Seung Cho; Sung-Ju Park; Kyungjun Song; Yun-ho Shin; Kookhyun Kim (Journal of Marine Science and Engineering)
Target strength (TS) is an important design factor for improving the survivability of an underwater vehicle, and various efforts are ongoing to enhance it. Among the design techniques to improve TS, absorbing materials attached to the surface of an underwater vehicle can play a key role by reducing the reflected and scattered acoustic waves. In this study, the acoustic performance of target strength absorbing materials (TSAMs) is first analyzed, and then the simplified procedure of TS analysis considering TSAMs is suggested. The 4-microphone method and transfer matrix method evaluating equivalent material properties of TSAMs are derived, and their effectiveness is cross-validated through a series of analyses for a multi-layer acoustic absorbing structure. From the observed results, it is concluded that the transfer matrix method is more suitable for practical TS analysis than the 4-microphone method because of the relatively low calculation and time costs required for the acoustic performance evaluations of TSAMs. In addition, a simplified TS analysis procedure considering the echo reduction (ER) and transmission loss (TL) is proposed based on the combining method of physical optics and geometric optics (PO/GO combined method) and equivalent material properties. Using the suggested procedure, a series of TS analyses are performed using the Benchmark Target Strength Simulation (BeTSSi) to validate its applicability and effectiveness.